STRATEGI PENULISAN HASIL PENELITIAN DALAM ARTIKEL ILMIAH UNTUK MENINGKATKAN KUALITAS PUBLIKASI AKADEMIK - Nurlina, Nina; Hayadi, Herawan; Apriyudin, Apriyudin; Haryati, Reti Sri; Putro, Muhammad Wachid Suryo; Nurlena, Elin (Jurnal Ilmiah Pendidikan dan Keislaman, 2026)
Writing scientific articles is one of the important skills in the academic world because it plays a role in disseminating research results and improving the quality of academic publications. However, many researchers, especially students, still have difficulty in compiling the results of the research in a systematic and clear manner. This study aims to analyze the strategy of writing research results in effective scientific articles to improve the quality of academic publications. This research uses a qualitative approach with the library research method. Research data was obtained from various scientific literature in the form of national and international journals relevant to research topics in the 2023–2025 range. The data collection technique is carried out through documentation studies, while the data analysis technique uses content analysis through the stages of data reduction, data presentation, and conclusion drawn. The results of the study show that effective strategies for writing research results in scientific articles include presenting objective, systematic, and clear data; the use of writing structures that are in line with the IMRAD model; as well as integration between data presentation, interpretation of results, and discussion of theory. In addition, the use of tables, graphs, and diagrams can also help clarify research findings so that it is easier for readers to understand the results of the research. Thus, the application of the right research writing strategy can improve the quality of scientific articles and increase the chances of publication in academic journals.